The impact of mobile device applications in the improvement of public transportation - Melo, P. (2022)
In order to achieve carbon emissions’ target imposed by the European commission, there were exceptional measures executed. The goal was to encourage the use of public transport in urban areas. It was assumed in this study that digitalization at the service of users and managers of public transport networks is a key instrument to improve their efficiency and attractiveness. Given the topicality and importance of the subject, it was pertinent to establish as the core goal of this work, not only the study of the currently used mobile applications within the urban areas of Lisbon and Porto, but also its impacts on the development of public transportation. Ultimately it was intended to identify among the users, the need for possible developments. As a methodology, an exploratory focus group was used at first. Therefore, it was possible to gain a comprehensive understanding on the users of public transports, their preferences, and which applications they most commonly use. Additionally, at the end of the focus group an inferential survey was also analyzed, amended and validated. This survey had the main objective of collecting the necessary data for analyzing the impact of an application for mobile devices, with the goal of improve the quality of public transport. After reviewing the results, it was possible to conclude that it exists a wide range of digital applications available on the market. In fact, these applications allow the mitigation of some transport problems/issues, thus improving the user experience of public means of transportation. This leads to the conclusion that it has a positive impact on the user. Finally, the need to improve current functions and even add new features was also identified.